Peningkatan Kesadaran Kesehatan Remaja melalui Platform Pembelajaran Berbasis Web di SMAN 2 Majalaya - Rosmalina Rosmalina; Siti Solihat Holida; Novianti Indah Putri; Devia Fitri Nopiani; Krisna Mulyadi; Siti Solihah (Universitas Muhammadiyah Semarang, 2026)
Adolescent health is an important component of national health development; however, it still faces challenges such as low health literacy, risky behaviors, and stigma related to reproductive and mental health. This community service program utilizes an interactive web-based learning platform to improve adolescent health literacy. The activities include program socialization, teacher and student training on platform use, user assistance, and evaluation through pre- and post-tests using a participatory approach. The results show an increase in students’ knowledge, with reproductive health rising from 55% to 91.7%, mental health from 53.3% to 93.3%, and drug-related knowledge from 56.7% to 91.7%. However, several healthy lifestyle behaviors still need improvement, particularly fruit and vegetable consumption, reading nutrition labels, and physical activity. Overall, the web-based learning platform supports the improvement of adolescent health literacy and strengthens health education in the school environment.